THE “SECOND WAVE” NIKKEI: A RESUMPTION OF THE JAPANESE EMIGRATION TO BRAZIL AFTER WORLD WAR II - Miteva, Boryana (Revista Inclusiones, 2019)
By the beginning of World War II a significant number of Japanese emigrants have left for Brazil as temporary workers. Emigration was planned, organized and funded at an interstate level and became an essential element of the Japanese-Brazilian cooperation. The war proved to be the most difficult period for the Japanese community in Brazil, as well as for the bilateral relations. In the postwar world defeated Japan strived to an economic and diplomatic recovery, while victorious Brazil sought a modernization.